2010
DOI: 10.1007/s11269-010-9685-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Changes of Lake Stages in Two Rapidly Urbanizing Watersheds

Abstract: Understanding changes induced by watershed urbanization is integral to developing an effective long-term management strategy. In this research, the authors study statistical changes of lake water surface levels in two urbanizing watersheds by evaluating serial change in time series parameters, autocorrelation, and variance as well as by developing a regression model to estimate weekly lake level fluctuations. The authors fit a seasonal integrated autoregressive moving average model to lake levels over subperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This downward trend in the highest potentiometric surface elevations could be a regional expression of less in ltration to groundwater due to an increase in impervious surfaces in the study area (Weng and Pu 2013). A study by Paynter et al (2011) found that urbanization reduces groundwater ow to lakes in this same area. Increasing groundwater withdrawals outside of well elds over the same period probably contributed to this effect as well (Geurink and Basso 2013, Fig.…”
Section: Discussionmentioning
confidence: 81%
“…This downward trend in the highest potentiometric surface elevations could be a regional expression of less in ltration to groundwater due to an increase in impervious surfaces in the study area (Weng and Pu 2013). A study by Paynter et al (2011) found that urbanization reduces groundwater ow to lakes in this same area. Increasing groundwater withdrawals outside of well elds over the same period probably contributed to this effect as well (Geurink and Basso 2013, Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The wetland serves to temporarily retain excess surface water during the wet season and releases it to streams during the dry season (Paynter et al 2011). However, because of the anthropogenic interference through canal dredging, channelization, and drainage it has resulted in fast movement of water to the downstream side entailing a risk of disconnectivity of groundwater dependent wetlands during extended dry seasons (Ali 2009).…”
Section: Introductionmentioning
confidence: 99%